Thermal Performance Analysis of Heat Exchanger Using Computational Fluid Dynamics - Rifqi, Andi Muhammad; Al-Khalil, Yusuf (RESWARA: Jurnal Riset Ilmu Teknik, 2025)
The increasing demand for high-efficiency thermal systems has intensified the development and optimization of heat exchangers across industrial, energy, and environmental applications. Computational Fluid Dynamics (CFD) has become a dominant tool for analyzing heat transfer and fluid flow behavior in complex heat exchanger geometries, enabling accurate prediction of thermal performance without extensive experimental costs. This study investigates the thermal performance of a shell-and-tube heat exchanger using CFD simulations to evaluate the effects of flow configuration, baffle spacing, and mass flow rate on heat transfer coefficient, temperature distribution, and pressure drop. Numerical simulations were conducted using ANSYS Fluent under steady-state turbulent flow conditions with water as the working fluid. The results indicate that counterflow configuration and optimized baffle spacing significantly enhance heat transfer while maintaining acceptable pressure losses. The obtained trends are consistent with previous studies, demonstrating improvements of up to 18–25% in heat transfer coefficient compared to baseline configurations. The findings confirm that CFD is a reliable and efficient tool for heat exchanger design optimization and provides valuable insights into thermal–hydraulic behavior, supporting its application in sustainable and energy-efficient thermal system development.